DIGITALIZATION OF THE COURT IN THE SETTLEMENT OF CASES - Yusep Mulyana (Magister Kenotariatan Universitas Pasundan, 2021)
Digitalization of information is the process of converting various information, news, or news from an analog format into a digital format so that it is easier to produce, store, manage, and distribute. Court services have been initiated since the issuance of the 2010-2035 judicial reform blueprint. The process of digitizing court services begins with document administration, with the application of the SIPP which then extends to case processing from registration to the issuance of decisions that have legal force. Electronic justice where all case related processes can be served on e-court and e-litigation applications. Applications in court can continue to develop along with the demands of the justice seekers' needs.